Phytoextraction of lead and arsenic from agricultural soils by different intercropping density of Boehmeria nivea (L.) and Pteris vittata (L.) - Wang, Dong; Zhu, ShouJing; Lu, YanWei; Zeng, Rui; Hu, ZhiXin; Li, Xiang; Jie, YuCheng (Agronomy journal, 2021)
This study aimed to analyze the heavy metal absorption characteristics of different plant species and planting patterns on lead (Pb) and arsenic (As) levels in soil. Two ramie [Boehmeria nivea (L.) Guad.] varieties (Zhongzhu‐1 and Xiangzhu‐3), and Pteris vittata L. were cultivated in monoculture and intercropping patterns in soil polluted with heavy metals (Pb and As). The plant traits and biomasses of Zhongzhu‐1 and Xiangzhu‐3 intercropped with P. vittata at a high density were not significantly different compared to their individual monoculture treatments. Meanwhile, the biomass of P. vittata intercropped with ramie was significantly reduced. In addition, the Pb content and Pb accumulation in shoots of Zhongzhu‐1 and Xiangzhu‐3 intercropped with P. vittata at high density significantly increased compared with the Pb content and Pb accumulation from monoculture shoots. The Xiangzhu‐3/P. vittata high density intercropping system had the highest Pb extraction at 232.14 g hm−2 and a Pb extraction efficiency of 0.0222%. The P. vittata monoculture system had the highest As extraction with 225.87 g hm−2 and an As extraction efficiency of 0.2765%. Moreover, ramie and P. vittata intercropping at high density was the most efficacious planting method for minimizing Pb–As pollution in soil with higher and effective remediation efficiency and economic benefit than monoculture planting system.